The impact of customer relationship management related critical success factors on customer satisfaction: an emprirical study of the banks in Malaysia - Jan, Muhammad Tahir (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2012)
The radical development in the banking sector of Malaysia has created a stiff competition among various banks. These banks need to satisfy the customers to the best for their sustainability. For this purpose, a strong relationship with customers is required. However, for strong relationship organizations are required to identify those factors which can be crowned responsible for it. This issue have raised a critical research agenda that requires attention to identify and test those factors which are crucial for the success of customer relationship. The present study, therefore, has set its objective in identifying and testing these critical factors for successful implementation of customer relationship management (CRM) in banking industry and investigating their impact on customer satisfaction. To accomplish this goal, the present research has explained related concepts and reviewed literature extensively on the topic. A research framework was developed based on a strong theoretical background. Accordingly, the empirical study was conducted in Klang valley in Malaysia, which is considered the hub of all banking activities. The target population of this study was employees of different banks. Further, data was also collected from selected customers for the purpose of measurement invariance only. Through selfadministered questionnaire 349 usable responses were acquired from employees and 161 usable responses from customers. Analysis of data was conducted using descriptive, exploratory and confirmatory factor analysis. After the satisfactory results of confirmatory factor analysis for all constructs, measurement invariance tests were conducted for customer satisfaction. Subsequently, structural equation modelling (SEM) was then employed to test the hypothesised relationships among the constructs, as postulated in the model. A total of twelve hypotheses were designed based on the review of the literature, out of which, nine were supported. The findings of this research revealed that technology related critical success factors (CSFs) significantly impact business process CSFs, privacy, trust, and customer satisfaction. It was also exposed that human related CSFs have a positive effect on business process CSFs. Further, it was revealed that privacy partially mediates the relationship between technology CSFs and trust. Similarly, the relationship between technology CSFs and customer satisfaction was also partially mediated by trust. Interestingly the findings also revealed that privacy has a direct positive effect on trust, whereas, trust has a direct positive effect on customer satisfaction. The findings of this research are valuable asset for the banking industry in Malaysia, especially those who are struggling to implement CRM successfully and also wish to enhance customer satisfaction. Academicians, practitioners, researchers, and policy-makers can also benefit from this research and its findings.